Exploration of clinical diagnosis for tendinopathy, tendon structure, and muscle strength in young elite female gymnasts: A 12-month follow-up study - Steinberg, N.; Elbaz, L.; Nemet, D.; Eliakim, A.; Dar, G. (Journal of Sports Sciences, 2025)
We aimed to examine the relationship between clinical diagnosis of tendinopathy, tendon structure, and muscle strength in 207 rhythmic, acrobatic and artistic elite female gymnasts over a period of 12 months (age 11.9 ± 1.8 years at baseline). Participants were assessed for patellar-tendon and Achilles-tendon structure, anthropometric parameters, and muscle strength, and were physically examined for clinical tendinopathy of the patella and the Achilles. At baseline, 26.6% and 31.4% of the gymnasts had clinical tendinopathy in the patellar or Achilles tendon, respectively. At follow-up, 37.2% and 38.6% remained healthy; 9.7% and 15.5% recovered; 36.2% and 30.0% developed clinical tendinopathy; and 16.9% and 15.9% remained with clinical tendinopathy, respectively. The healthy and recovered groups exhibited decreased prevalence of disorganised patellar tendon and Achilles tendon fibres from baseline to follow-up, while those who sustained or had developed tendinopathy showed increased prevalence (p < 0.05). A high prevalence of clinical tendinopathy was observed among adolescent female gymnasts, with a limited chance of recovery. At baseline, gymnasts without tendinopathy exhibited higher muscle strength and lower prevalence of disorganised tendon fibres than gymnasts with tendinopathy. At follow-up, recovered gymnasts exhibited higher muscle strength and lower prevalence of disorganised tendon fibres than those who had sustained or developed tendinopathy.